The relationship between Malaysian and major world stock market / Nur Faridah Zaidi - Zaidi, Nur Faridah (Faculty of Business Management, 2017)
It is well known that many countries around the world depend on the US as their major trade partner. As a result, if something does happen to US stock market it surely will affect the others stock market. In this study, I investigate the relationship between Malaysia and international stock market namely U.S, U.K, Korea, Singapore, and Japan using daily data for the period 27 February 2009 until 31 December 2015. In order to find out the result there are six tests was using which is Descriptive test, Normality test, Unit root test, Pearson correlation, Regression, and White test. From the test all the three objectives was answered when there are positive relationship between KLCI and major world stock market while the most risky toward volatility of the stock are FTSE Straits Times Index and Nikkei 225 if compared to four other stock.